Short‐term rapamycin administration elevated testosterone levels and exacerbated reproductive disorder in dehydroepiandrosterone‐induced polycystic ovary syndrome mice - Zaixin Guo; Xiaohan Chen; Penghui Feng; Qi Yu (BMC, 2021)
Abstract Background Polycystic ovary syndrome (PCOS) is a multifactorial endocrinopathy that affects reproduction and metabolism. Mammalian target of rapamycin (mTOR) has been shown to participate in female reproduction under physiological and pathological conditions. This study aimed to investigate the role of mTOR complex 1 (mTORC1) signaling in dehydroepiandrosterone (DHEA)-induced PCOS mice. Results Female C57BL/6J mice were randomly assigned into three groups: control group, DHEA group, and DHEA + rapamycin group. All DHEA-treated mice were administered 6 mg/100 g DHEA for 21 consecutive days, and the DHEA + rapamycin group was intraperitoneally injected with 4 mg/kg rapamycin every other day for the last 14 days of the DHEA treatment. There was no obvious change in the expression of mTORC1 signaling in the ovaries of the control and DHEA groups. Rapamycin did not protect against DHEA-induced acyclicity and PCO morphology, but impeded follicle development and elevated serum testosterone levels in DHEA-induced mice, which was related with suppressed Hsd3b1, Cyp17a1, and Cyp19a1 expression. Moreover, rapamycin also exacerbated insulin resistance but relieved lipid metabolic disturbance in the short term. Conclusions Rapamycin exacerbated reproductive imbalance in DHEA-induced PCOS mice, which characterized by elevated testosterone levels and suppressed steroid synthesis. This underscores the need for new mTORC1-specific and tissue-specific mTOR-related drugs for reproductive disorders.